PELLETED FIELD GRASS TO INCREASES THE JAVA THIN TAIL SHEEP PRODUCTIVITY - Widiyanto, W.; Surahmanto, S.; Mulyono, M.; Kusumanti, E. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
This investigation was conducted to study the influence of the pelleted field grass (FG) toperformance of Java thin tail (JTT) sheep. Twelve heads of male JTT sheep were devided into 3 groups,consisted of 4 heads as replication, respectively. There were three kinds of ration as treatments, namely:fresh FG (T0), pelleted FG (T1), and combination between 85% FG and 15% rice bran (T2). Themeasured variables were: feed dry matter (DM) consumption, in vivo dry matter digestibility (IVoDMD)and in vivo organic mattter digestibility (IvoOMD), molar proportion of partial volatile fatty acids(VFAs), and daily body weight gain (DBWG). Data were analyzed by analysis of variance (ANOVA) incompletely randomized design (CRD). Result of this investigation showed hat feed consumption bysheep received pelleted FG was higher (P< 0.05) than those received FG (513 vs 393 g). Ratio of aceticacid : propionic acid in sheep received pelleted FG was lower (P<0.05) than those in sheep received FG(2.53 vs 3.46). Feeding of the pelleted FG resulted in DBWG significantly differed from combinationbetween FG and rice bran (69 and 72 g), and were higher (P<0.05) than feeding of FG (53 g). Inconclusion, the feeding of pelleted FG resulted the higher DM consumption and ruminal propionic acid,the lower acetic acid : propionic acid ratio, than feeding of fresh FG. Feeding of pelleted FG to male JTTsheep increased the DBWG, equivalent to those by feeding of combination between 85% fresh FG an15% rice bran.